Probability of brick structures destruction (Academic journal Industrial Machine Building Civil Engineering, 2019)
The results of calculations of construction brick destruction probability determination at central and off-center compressionare given; the determination of the brick structures destruction probability, caused by the exhaustion of the masonry strengthon local compression (crushing); determination of the brick structures destruction probability associated with the exhaustionof the masonry strength on the displacement (cut); determination of the brick structures destruction probability associatedwith the exhaustion of the masonry strength on the fold, the stretch; determination of the brick structures destruction probabilityon the crack opening. The value of the security characteristic for each case has been determined and the comparisonwith the normative values has been made.
Keywords: limit state of the system; integral model of reliability estimation; the Monte Carlo method; refusal model; system reliability; system; brick construction